Optimizing Home Yards as an Effort to Ensure Family Food Security in Villages - Harahap, Rahma Hayati; Saladin, T. Ilham; Sudarwati, Lina (Research Horizon, 2024)
The role of women to be important in an attempt creating food security. Woman in families in general, ensuring that access to food is sufficient, safe and nutritious for every member family. Contribution concrete from role Woman in development is its membership through roles and participation in Women's Groups Farmers. One of the Women Farmers Groups that has a role in food security family is Group Woman Farmer Aisyiyah Which is at in Desa Sei Rotan. The potential of Desa Sei Rotan in this case is the availability of extensive land so that its utilization... Good land can have a big impact on society. Empowerment activities Group Woman Farmer Aisyiyah aiming for increase knowledge, skills, and independence Group Woman Farmer in optimize yard to create family food independence and economic income. The goal is housewives who are active members of the Aisyiyah Women Farmers Group use method counseling, training and mentoring with approach Participatory Rural Appraisal (PRA). Approach PRA done with method involving community participation in planning and formulating problems experienced by community. The PRA approach is the right choice to provide opportunities for women to be active in empowerment activities and increase their role in family and public.